Algorithms push forward the application of MALDI–TOF mass fingerprinting in rapid precise diagnosis. Issue 2 (11th January 2023) - Zhu, Yingdi; Girault, Hubert H.
Abstract: Macromolecular mass fingerprinting using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry is a quick tool for biochemical analysis. In combination with algorithms for automated data analysis and interpretation, it has wide application potentials in life science, especially for diagnostic purposes. This review aims to illustrate recent advances of this analytical tool, focusing on the improvement of the experimental techniques, the data analysis algorithms, and more importantly the applications in rapid precise diagnosis. Abstract : Macromolecular mass fingerprinting using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry is a quick tool for biochemical analysis. In combination with algorithms for automated data analysis and interpretation, it has wide application potentials in life science, especially for diagnostic purposes. This review aims to illustrate recent advances of this analytical tool, focusing on the improvement of the experimental techniques, the data analysis algorithms and more importantly the applications in rapid precise diagnosis.